2010
DOI: 10.4314/gmj.v43i3.55334
|View full text |Cite
|
Sign up to set email alerts
|

Causes and incidence of destructive eye procedures in north-eastern Ghana.

Abstract: Objective: To determine the causes and incidence of destructive ophthalmic procedures as seen at a major reference eye centre in northern Ghana Methods: Retrospective case series involving a review of surgical records of all evisceration and enucleation procedures done between January 2002 and December 2006 at the Bawku Hospital Eye Department. Information collected included basic demographic data, diagnosis, visual acuity at diagnosis and the eye affected. The aetiology responsible was determined from history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 6 publications
2
14
0
1
Order By: Relevance
“…However, Bodunde et al (2005) in Nigeria reported the mean age of 29.69 ± 16.93 years among their patients. The male preponderance in our study was similar to that of other studies (Etebu and Adio, 2008;André et al, 2011;Epee et al, 2008 ;Gyasi et al, 2009;Bodunde et al, 2005). The most affected age group was 0 -10 years similar to that of other studies in Cameroon (André et al, 2011) and China (Cheng et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Bodunde et al (2005) in Nigeria reported the mean age of 29.69 ± 16.93 years among their patients. The male preponderance in our study was similar to that of other studies (Etebu and Adio, 2008;André et al, 2011;Epee et al, 2008 ;Gyasi et al, 2009;Bodunde et al, 2005). The most affected age group was 0 -10 years similar to that of other studies in Cameroon (André et al, 2011) and China (Cheng et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…The mean age of our patients was 36.69 years, which is similar to the previous studies in Africa on DOS (Etebu and Adio, 2008;André et al, 2011;Epee et a., 2008 ;Gyasi et al, 2009). However, Bodunde et al (2005) in Nigeria reported the mean age of 29.69 ± 16.93 years among their patients.…”
Section: Discussionsupporting
confidence: 89%
“…The application of home remedies such as herbal preparations, urine, breast milk, onions and kerosene to treat eye conditions is a common occurrence in Nigeria and other parts of Africa [11][12][13] . The consequence of this unorthodox practice is avoidable blindness often from significant corneal morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The application of home remedies such as herbal preparations, urine, breast milk, onions and kerosene to treat eye conditions is a common occurrence in Nigeria and other parts of Africa [11][12][13] . The consequence of this unorthodox practice is avoidable blindness often from significant corneal morbidity.…”
Section: Discussionmentioning
confidence: 99%